A Bibliometric Review of Palm Oil Price Volatility and Its Macroeconomic Impacts in Southeast Asia - Judijanto, Loso (West Science Interdisciplinary Studies, 2025)
Palm oil plays a pivotal role in the economic landscape of Southeast Asia, particularly in countries like Indonesia and Malaysia where it significantly contributes to GDP, employment, and trade revenues. However, the volatility of palm oil prices presents persistent challenges, affecting macroeconomic stability, food security, and policy planning. This study presents a comprehensive bibliometric analysis of the scholarly literature on palm oil price volatility and its macroeconomic impacts, focusing on Southeast Asia from 2000 to 2024. Using the Scopus database and VOSviewer software, the analysis reveals key thematic clusters centered on economic costs, price dynamics, biofuel policy, and financial spillover effects. The results show a growing interdisciplinary trend, with research expanding from core economic modeling toward sustainability and energy policy frameworks. Overlay and density visualizations indicate a temporal shift in research focus from volatility analysis to broader systemic and policy-related issues. Despite the increasing depth and diversity of the literature, significant gaps remain, particularly in addressing the socio-environmental dimensions and the real-world impacts on smallholder farmers and national policy. This review not only maps the intellectual structure of the field but also offers critical insights for future research and evidence-based policymaking in the global palm oil economy.